111In-Oxine-WBC SPECT/CT of Lumbosacral Facet Joint Septic Arthritis. (January 2021) - Zamora, Edgar; Valdivia, Ana Y.; Kumar, Arun; Chun, Kwang J.
Abstract : Abstract: Spinal facet joint septic arthritis is a rare pathology associated with pyogenic organisms. It may present in older adults with back pain, fever, and positive bacterial blood cultures. However, clinical presentation may be equivocal, and diagnosis relies on anatomic imaging for differentiation from other pathologies. Magnetic resonance is considered the imaging modality of choice and has been found superior to CT; however, it is unable to differentiate facet joint septic arthritis from other inflammatory arthropathies. We present a case of lumbosacral facet joint septic arthritis as seen on 111 In-oxine-WBC scintigraphy and SPECT/CT.